An Ultrasensitive Electrochemical Sensor Based on Multiwalled Carbon Nanotube@Reduced Graphene Oxide Nanoribbon Composite for Simultaneous Determination of Hydroquinone, Catechol and Resorcinol. Issue 6 (17th April 2019) - Yang, Siyi; Yang, Mei; Liu, Qingyan; Wang, Xiaojing; Fa, Huanbao; Wang, Yongzhong; Hou, Changjun
Abstract : Three dihydroxybenzene isomers, hydroquinone (HQ), catechol (CC) and resorcinol (RS), were determined simultaneously by an ultrasensitive electrochemical sensor based on a glassy carbon electrode modified by multiwalled carbon nanotube@reduced graphene oxide nanoribbon (MWCNT@rGONR) composite. The material was synthesized via hydrothermal method and characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD). We used cyclic voltammetry (CV) to study the electrochemical performance of the three isomers and differential pulse voltammetry (DPV) to optimize the experimental parameters. Based on the optimal experimental condition, our electrochemical sensor displayed a good linear relationship with the concentration range of 15 to 921 μM, 15 to 1101 μM, and 15 to 1301 μM and detection limit of 3.89 μM, 1.73 μM and 5.77 μM for HQ, CC and RS respectively. The electrochemical sensor based on MWCNT@GONR composite showed outstanding ability of reproducibility, stability and anti-interference. In addition, this sensor was also used successfully for simultaneous determination of HQ, CC and RS in real samples with satisfactory result.